Arsenic diffusion in boron‐doped germanium. Issue 2 (1st January 2013) - Liu, T.; Orlowski, M. K.
Abstract : Arsenic (As) diffusion in germanium (Ge) has been studied by implanting As in a Ge substrate with high boron (B) background doping. The high hole density induced by the B doping suppresses negatively charged vacancies (V) in Ge. Under this condition, we have investigated the dependence of As diffusion on the dopant‐vacancy pairs As + V 0 by secondary ion mass spectroscopy. After rapid thermal annealing at 600−750°C, the chemical profiles of As do not change in the highly B doped Ge. Experimental results suggest that the As + V 0 pairs are not the diffusion vehicles of As in Ge. Activation energy of the As + V 0 pairs has to be larger than 3.25 eV.